A preparation of nitric acid from nitrogen dioxides using photocatalytic method - Aizuddin, Abdul Malek (2010)
A research is conducted to study on preparation of nitric acid from nitrogen dioxides using photocatalytic method. Due to the increasing pollution of oxides of nitrogen (NOx), production of nitric acid is vital in reducing the oxides of nitrogen release to the atmosphere. Nitric acids are one of the most important inorganic acids and commonly used as laboratory reagent and an important industrial commodity. Moreover, oxides of nitrogen are the major contributors to acid rain and ground-level ozone pollution. The main objective is to convert from waste to wealth by preparing nitric acid from industrial waste which is nitrogen dioxides. A photo-reactor with 1000 watt Metal Halide Lamp was used to optimize the production of nitric acid. The result from the experiment will be analyze and compared with the pure nitric acid. This method is efficient and economical.